Implementing Arabic Song Videos to Improve Student Learning Outcomes at MI Plus Al Munjiyat Kediri - Faruq, Ahmad Umar; Fuad, Muhammad Sabitul; Maulidi, Maulidi; Jaya, Dwi Umar (Kitaba, 2025)
Abstract: This study aimed to describe the process of implementing Arabic song videos and find out their impact on student learning outcomes at MI Plus Al Munjiyat Kediri City. The researcher conducted Classroom Action Research (CAR) on 15 students in Grade VI. In the learning process, students were invited to learn Arabic while singing vocabulary and sentences through videos, so that learning became more creative, fun, and easy to understand. The researcher used tests, observations, and documentation to collect data, then analyzed the differences in average learning outcomes before and after the video was implemented. The results showed a significant increase in the average student score, from 42.7 in the pre-test to 87.9 in the post-test. This occurred because the use of videos and songs made students more active, enthusiastic, and able to understand the material more easily. In addition to the cognitive aspect, the motivational and student participation aspects also improved. Thus, the use of Arabic song videos proved to be a creative and useful learning medium, not only for achieving learning goals but also for creating a lively, fun, and meaningful learning atmosphere for students.Keywords: Learning Videos; Arabic Songs; Student Learning Outcomes